2021
DOI: 10.1111/1742-6723.13854
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives of emergency department clinicians on the challenges of addressing low back pain in the emergency setting: A qualitative study

Abstract: Objective: To identify and explore ED clinician perspectives on: (i) why patients with low back pain (LBP) present to the ED and are admitted into hospital from ED; (ii) barriers and enablers they face when providing care to patients with LBP; and (iii) strategies to improve the care of patients with LBP, and associated care processes, in the ED. Methods: We undertook a qualitative exploratory study with ED clinicians (medical officers, nurses and physiotherapists) at a tertiary-level public hospital in New So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Low back pain (LBP) is one of the complex bio-psychological health conditions that challenge clinicians in the developed world. 1 The cost of this condition is quite high and data from European countries have suggested the cost varies between 0.1-2%. 2 However; no data is available from low and middle-income countries.…”
Section: Introductionmentioning
confidence: 99%
“…Low back pain (LBP) is one of the complex bio-psychological health conditions that challenge clinicians in the developed world. 1 The cost of this condition is quite high and data from European countries have suggested the cost varies between 0.1-2%. 2 However; no data is available from low and middle-income countries.…”
Section: Introductionmentioning
confidence: 99%
“…4,6,7 Relatively little is known about longitudinal patterns of all types of HCPs involved in an episode of LBP and association with guideline concordance and total cost. Research into the sequence of types of HCPs involved in an episode of LBP has tended to focus on service use rather than types of HCPs involved, and has often focused on a single type of initial contact HCP such as PCP 9,10 , physiatry 11 , emergency medicine (EM) 12,13 , and PT. 5,8,14 These studies identified variation in approaches to LBP, yet have not provide comprehensive insights into patterns of HCP involvement in LBP.…”
Section: Introductionmentioning
confidence: 99%
“…Some barriers reported by ED clinicians include fear of missing serious pathology, severe physical limitation, lack of physiotherapy staff in ED, lack of awareness or availability of alternate pathways, and performance-based targets such as the ED four-hour standard. 10 People from minority ethnic groups, and those not fluent in the majority language have increased risk of admission and prolonged length of stay. 6 Hospitalisation in these cases may be requested to obtain objective test results and screen for underlying serious condition, which suggests that clinician-patient communication plays a crucial role in this process.…”
mentioning
confidence: 99%